KLASIFIKASI WAKAF PRODUKTIF MENGGUNAKAN ALGORITMA ID3 PADA SISTEM INFORMASI ASET DAN KEHARTABENDAAN MAJELIS WAKAF YOGYAKARTA - Muhammad Munsarif (Universitas Asahan, 2020)
Abstract – Productive Waqf is one of the waqf management programs developed in the modern era to improve the Islamic economy. The large number of waqf land received by nazir from year to year causes the management of waqf to be more complicated. This is caused by the lack of financial support and based on data from the ministry of religion in April 2020 the area of waqf land is 50,260.89 Ha. The waqf information system that has been developed has not been able to be a solution to the problems of waqf land management. Muhammadiyah which is the oldest Islamic organization that has succeeded in making many charitable efforts using waqf still not able to overcome the existing problems. The amount of waqf that is owned by Muhammadiyah requires an analysis to make a classification of productive and non-productive endowments that can provide information to make decisions in the management of endowment management on an ongoing basis. In this research, the ID3 algorithm is used for waqf classification which can show productive and non-productive categories using data derived from Muhamamdiyah Asset Information System in the Yogyakarta region. The results of the study provide recommendations that are shown in the decision tree produced by ID3 so that it can be concluded that for the management of waqf it is necessary to group and classify productive and non-productive land to create a professional endowment management plan.Keywords: Decision Support System, ID3 Algorithm, Data Mining, Waqf information system, Productive Waqf, Muhammadiyah, Rapidminner.Abstract – Wakaf produktif menjadi salah satu program pengelolaan wakaf yang dikembangkan di era modern dengan tujuan untuk meningkat perekonomian umat islam.Besarnya Jumlah wakaf tanah yang diterima oleh para nadzir dari tahun ke tahun menyebabkan pengelolaan wakaf menjadi lebih rumit.Hal ini di sebabkan tidak adanya dukungan pembiayaan dan pengembangannya.Berdasarkan data dari kementerian agama pada April 2020 luas tanah wakaf 50.260.89 Ha .Sistem informasi wakaf yang telah dikembangkan belum mampu menjadi solusi atas permasalah pengelolaan tanah wakaf .Muhammadiyah yang merupakan organisasi Islam tertua yang telah berhasil membuat banyak amal usaha dengan menggunakan wakaf masih belum mampu mengatasi persoalan yang ada.Besarnya wakaf yang di miliki oleh muhammadiyah membutuhkan sebuah analisa untuk membuat klasifikasi wakaf produktif dan non produktif yang mampu memberikan informasi untuk membuat keputusan dalam perencanaan pengelolaan wakaf secara berkesinambungan. Pada penelitian ini Algoritma ID3 digunakan untuk klasifikasi wakaf yang mampu menunjukan kategori produktif dan non produktif dengan menggunakan data yang berasal dari Sistem informasi aset Muhamamdiyah wilayah Yogyakarta. Hasil penelitian memberikan rekomendasi yang di tunjukkan dalam pohon keputusan yang di hasilkan oleh ID3 ,Sehingga bisa simpulkan bahwa untuk pengelolaan wakaf di butuhkan pengelompokan dan klasifikasi tanah produktif dan non produktif dalam upaya membuat rencana pengeloaan wakaf secara profesional.Kata kunci: Sistem Pendukung Keputusan, Algoritma ID3, Data Mining, Sistem Informasi Wakaf, Wakaf Porduktif, Muhammadiyah, Rapidminner